Correlation of serum PDCD5 and Bax contents with the pathological features of tumor lesions in patients with lung cancer - Qian Huang (Journal of Hainan Medical University, 2018)
Objective: To study the correlation of serum PDCD5 and Bax contents with the pathological features of tumor lesions in patients with lung cancer. Methods: Patients with lung cancer who underwent surgical treatment in West China Hospital between June 2014 and March 2017 were selected as the lung cancer group for the study, the serum specimens were collected before surgery, and the lung cancer lesion and adjacent lesion were taken after surgery; the healthy subjects who underwent physical examination in West China Hospital during the same period were selected as the control group, and the serum samples were taken during the physical examination; the contents of PDCD5 and Bax in serum as well as the contents of PDCD5 and Bax, and the expression of proliferation genes and invasion genes in the lung cancer lesion and adjacent lesion were measured. Results: PDCD5 and Bax contents in serum of lung cancer group were significantly lower than those of control group, PDCD5 and Bax contents in lung cancer lesion were significantly lower than those in adjacent lesion, and the PDCD5 and Bax contents in serum of patients with lung cancer were positively correlated with the PDCD5 and Bax contents in lung cancer lesion; C-myc, RACK1, CatL, MMP2 and N-cadherin mRNA expression in lung cancer lesion were significantly higher than those in adjacent lesion and negatively correlated with PDCD5 and Bax contents in serum whereas LAST1, PAQR3, TCF21, E-cadherin, TIMP1 and TIMP2 mRNA expression were significantly lower than those in adjacent lesion and positively correlated with PDCD5 and Bax contents in serum. Conclusion: The decrease of PDCD5 and Bax in serum of patients with lung cancer is closely related to the aggravation of cancer cell proliferation and invasion in tumor lesions.